The Role of Corporate Governance in Firm’s Stock Performance - Farooq, Kiran; Salman, Syed Muhammad; Ali, Nasir; Hassan, Muhmmad; Aziz, Atif (iRASD Journal of Economics, 2023)
The Increasing trend of globalization and stock volatility attracts academic researchers to investigate the causes. As the economic globalization has radically increased, there is a need to know more about corporate governance. The shareholder’s pattern of firms gives an understanding of corporate control and good governance. These aspects provide the researcher with an explanation of how shareholder behavior may influence the market volatility and valuation. To analyze the impact of the firm’s ownership structure on market performance of firm, the ownership structure is decomposed by the percentage of equity. Whereas market to book ratio and stock volatility for market performance. We use the sample of 192 companies, from the period of 2006 to 2018. The study used different suitable statistical technique such as “correlation, multiple regression analysis”. The statistical analysis indicates that foreign ownership significantly reduces the stock volatility and enhances the firm’s stock valuation compared to its book value. Director ownership is a cause of rising stock volatility and it could not play a significant role in enhancing firm’s stock valuation. This research will also provide the critical recommendation for academics and for economic growth.